2005
DOI: 10.1086/428450
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Reactivity of Anti–HIV‐1 T Cell Immune Responses among the Major HIV‐1 Clades in HIV‐1–Positive Individuals from 4 Continents

Abstract: Cross-clade reactivity of cellular immune responses can be substantial but varies by viral protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 37 publications
2
33
0
Order By: Relevance
“…7C) most likely the consequence of the internalization of shed viral proteins. This assay was significant because Gag and Nef proteins are expected to be the viral products most commonly recognized by effector lymphocytes from HIV-1-infected patients [25][26][27][28]. We confirmed this finding by evaluating the HIV-1 Ag-presenting activity of iDC infected with WT or Denv HIV-1 in the presence of AZT (data not shown).…”
Section: High Levels Of Hiv-1 Endocytosis Correlate With Strong Hiv-1supporting
confidence: 61%
“…7C) most likely the consequence of the internalization of shed viral proteins. This assay was significant because Gag and Nef proteins are expected to be the viral products most commonly recognized by effector lymphocytes from HIV-1-infected patients [25][26][27][28]. We confirmed this finding by evaluating the HIV-1 Ag-presenting activity of iDC infected with WT or Denv HIV-1 in the presence of AZT (data not shown).…”
Section: High Levels Of Hiv-1 Endocytosis Correlate With Strong Hiv-1supporting
confidence: 61%
“…Putatively, the generation of consensus sequences will erase functional HLA anchor residues and thus explain the distinction seen between the peptide pools. However, in a large recently conducted study (250 patients) (16), intraclade responses were found to be higher than interclade responses using the same reagents, leading to a probable dilution of the aforementioned phenomenon. These results prompted us to analyze amino acid variation in reported CTL epitopes.…”
Section: Discussionmentioning
confidence: 87%
“…While CD8 ϩ T-cell cross-clade recognition has been tested extensively (6,11,19,36,48), few studies have addressed the possibility of clade-specific escape from CD8 ϩ T-cell responses. This may be especially relevant where clade consensus sequences differ in immunologically relevant epitopes.…”
Section: Hiv-specific Cd8mentioning
confidence: 99%